CO(2–1)/CO(1–0) Line Ratio on a ∼100 Parsec Scale in the Nearby Barred Galaxy NGC 1300 - Maeda, Fumiya; Egusa, Fumi; Ohta, Kouji; Fujimoto, Yusuke; Habe, Asao; Asada, Yoshihisa (The Astrophysical journal, 2022)
CO(2–1) emission is often used as a tracer of giant molecular clouds (GMCs) as an alternative to CO(1–0) emission in recent years. Therefore, understanding the environmental dependence of the line ratio of CO(2–1)/CO(1–0), R 21 , on the GMC scale is important to accurately estimate the mass of GMCs. We thus measured R 21 in the strongly barred galaxy NGC 1300, where star formation activity strongly depends on galactic structure, on a ∼100 pc scale. CO images were obtained from the Atacama Large Millimeter/submillimeter Array and the Nobeyama 45 m telescope. The resultant typical R 21 in NGC 1300 is 0.57 ± 0.06. We find environmental variations in R 21 : it is the highest in the bar-end region (0.72 ± 0.08), followed by arm (0.60 ± 0.07) and bar regions (0.50 ± 0.06). GMCs with H α emission show a systematically higher ratio (0.67 ± 0.07) than those without H α (0.47 ± 0.05). In the bar region, where massive star formation is suppressed, H α emission is not associated with most GMCs, resulting in the lowest R 21 . These results raise a possibility that properties of GMCs derived from CO(2–1) observations with the assumption of a constant R 21 are different from those derived from CO(1–0) observations. Furthermore, we find the R 21 measured on the kiloparsec scale tends to be lower than that of the GMCs, probably due to the presence of an extended diffuse molecular gas in NGC 1300.